2021
DOI: 10.1002/aisy.202100205
|View full text |Cite
|
Sign up to set email alerts
|

Memristor Circuits for Colloidal Robotics: Temporal Access to Memory, Sensing, and Actuation

Abstract: Micrometer‐scale robots capable of navigating enclosed spaces and remote locations are approaching reality. However, true autonomy remains an open challenge despite substantial progress made with externally supervised and manipulated systems. To accelerate the development of autonomous microrobots, alternatives to conventional top‐down lithography are sought. Such additive technologies like printing, coating, and colloidal self‐assembly allow for rapid prototyping and access to novel materials, such as polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 133 publications
(162 reference statements)
0
11
0
Order By: Relevance
“…Genetically engineered bacteria has shown quantifiable swarm behaviors in response to the temperature, humidity, and concentration of chemicals, thereby proving the concept of swarm-based information encoding and decoding . Electronically integrated microagents , and colloidal state machines (i.e., micro/nanoscale colloidal particles with electronic materials) , have been fabricated despite the challenges in the integration of onboard processors, sensors, actuators, power sources, and communication modules on a single micro/nanoagent, and computational studies have shown that a swarm of memristor-integrated microagents can be capable of achieving automated regulation of glucose . In the future, circuit-integrated micro/nanoagents would endow micro/nanorobotic swarms with enhanced intelligence for autonomy to circumvent external guidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically engineered bacteria has shown quantifiable swarm behaviors in response to the temperature, humidity, and concentration of chemicals, thereby proving the concept of swarm-based information encoding and decoding . Electronically integrated microagents , and colloidal state machines (i.e., micro/nanoscale colloidal particles with electronic materials) , have been fabricated despite the challenges in the integration of onboard processors, sensors, actuators, power sources, and communication modules on a single micro/nanoagent, and computational studies have shown that a swarm of memristor-integrated microagents can be capable of achieving automated regulation of glucose . In the future, circuit-integrated micro/nanoagents would endow micro/nanorobotic swarms with enhanced intelligence for autonomy to circumvent external guidance.…”
Section: Discussionmentioning
confidence: 99%
“…386 Electronically integrated microagents 387,388 and colloidal state machines (i.e., micro/nanoscale colloidal particles with electronic materials) 389,390 have been fabricated despite the challenges in the integration of onboard processors, sensors, actuators, power sources, and communication modules on a single micro/nanoagent, and computational studies have shown that a swarm of memristor-integrated microagents can be capable of achieving automated regulation of glucose. 391 In the future, circuit-integrated micro/nanoagents would endow micro/nanorobotic swarms with enhanced intelligence for autonomy to circumvent external guidance. Overall, with the close collaboration among researchers with expertise across diverse fields, the next decade will witness a multitude of such advances in micro/nanorobotic swarms to fully realize their potential.…”
Section: Discussionmentioning
confidence: 99%
“…By relying on our system's self-organised behaviours, we circumvented the design of complex contraptions to harvest and transduce chemical energy into periodic electrical and mechanical work-a crucial step towards fully-autonomous microrobots 62,64 . The use of on-board electrical currents will enable the integration of sensors and computational elements to enrich physical microparticle interactions 65 , forming the basis for future collectives wherein the long-envisioned potential of complex interparticle communications can be implemented 40 . We plan on extending our approach into studying larger collections of microparticles in search of general principles for the top-down design of active matter systems, where an understanding of system symmetries and environmental forcing may enhance their task-capability.…”
Section: Discussionmentioning
confidence: 99%
“…By relying on our system's self-organized behaviours, we circumvented the design of complex contraptions to harvest and transduce chemical energy into periodic electrical and mechanical worka crucial step towards fully-autonomous microrobots [75,76]. The use of on-board electrical currents will enable the integration of sensors and computational elements to enrich microparticle interactions [77], forming the basis for future collectives wherein complex inter-particle communication can be implemented. We plan on extending our approach into studying larger collections of microparticles in search of general principles for the top-down design of active matter systems, where an understanding of system symmetries and environmental forcing may enhance their task-capability.…”
Section: Discussionmentioning
confidence: 99%